2021
DOI: 10.1016/j.annonc.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA in neoadjuvant-treated breast cancer reflects response and survival

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
168
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 253 publications
(220 citation statements)
references
References 51 publications
17
168
1
Order By: Relevance
“…We have previously shown that pretreatment ctDNA (as binary or continuous variable) was associated with subtype, clinical T stage, and MammaPrint score (as risk categories MammaPrint high 1 and high 2) 16 . Here, we examined associations between pretreatment FTV and clinicopathologic variables.…”
Section: Ctdna Ftv and Clinicopathologic Variablesmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that pretreatment ctDNA (as binary or continuous variable) was associated with subtype, clinical T stage, and MammaPrint score (as risk categories MammaPrint high 1 and high 2) 16 . Here, we examined associations between pretreatment FTV and clinicopathologic variables.…”
Section: Ctdna Ftv and Clinicopathologic Variablesmentioning
confidence: 99%
“…Hormone receptor (estrogen and progesterone) and HER2 status, and MammaPrint risk classification (MammaPrint high 1 and high 2) based on a 70-gene signature test were assessed at pretreatment. ctDNA was detected using a personalized and a tumor-informed multiplex PCR next generation sequencing platform (Signatera TM bespoke mPCR-NGS assay) as previously described 16 . Briefly, the test's tumorinformed approach allowed for the detection of ctDNA by tracking up to 16 clonal variants (i.e., targets) in plasma.…”
Section: Data Acquisitionmentioning
confidence: 99%
See 3 more Smart Citations